Unveiling Legal and Religious Divergence: Abandoned Husband Divorce in Indonesian and Syrian Contexts - Rahmawati, Dewi; Trigiyatno, Ali; Faqih, Muhammad Ikhsanul; Arifudin, Mohamad; Mufid, Abdul; Aland, Ahmed Orhan (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2023)
This study seeks to analyze and contrast the fiqh provisions and legal regulations pertaining to a wife's right to seek divorce in Indonesia and Syria, specifically in cases where the husband is absent. The author aims to employ a normative approach and comparative approaches, together with data analytic techniques like as text analysis, to identify both parallels and discrepancies between fiqh provisions and laws in Indonesia and Syria. Indonesian and Syrian state legislation predominantly aligns with the viewpoints of the Shafi'i, Hanbali, and Maliki schools of thought, which permit the possibility of challenging a divorce on the grounds of the husband's absence. From the two countries, specifically Indonesia and Syria. Indonesia has established the record for the greatest duration of being missing or unseen, spanning two continuous years. Subsequently, Syria undergoes a period of absence or invisibility lasting for one year. During the specified timeframe for assessing the divergence between the nations of Indonesia and Syria, the majority of individuals have not adhered to the teachings of the fiqh scholars. The Shafi'i, Hanbali, and Maliki schools establish a four-year time frame within which a wife may wait for her missing husband. Both Indonesia and Syria share similar provisions regarding the dissolution of a marriage due to an absent husband. Specifically, they consider an absent husband as one of the reasons that can lead to the termination of a marriage. Additionally, these countries also prohibit a wife whose husband is absent from remarrying until a court decision has been made.